1995
DOI: 10.1203/00006450-199505000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chest Wall Distortion and Esophageal Catheter Position on Esophageal Manometry in Preterm Infants

Abstract: The purpose of this stud y was to determine the effect of chest wall distortion on esophageal manometry by measuring simultaneous esophageal pressure changes at two sites in preterm infants . Fourteen infants were studied (mean ± SD: birth weight, 1340 ± 260 g; age, 8.5 ± 4 d). Esoph ageal pressure was measured through two water-filled catheters, one placed just above the cardia (Pes1) and the other at the level of the carina (Pes2) . Chest wall distortion was measured by inductance plethysmography, and inspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…26,27 However, there is evidence to suggest that many of the esophageal manometry relate to the use of unsuitable tools rather than uneven pleural pressure. 28 For ethical reasons it is no longer permissable to withhold exogenous surfactant from infants with RDS. Hence, it was not possible to make a comparison between surfactant-treated and untreated or placebotreated infants.…”
mentioning
confidence: 99%
“…26,27 However, there is evidence to suggest that many of the esophageal manometry relate to the use of unsuitable tools rather than uneven pleural pressure. 28 For ethical reasons it is no longer permissable to withhold exogenous surfactant from infants with RDS. Hence, it was not possible to make a comparison between surfactant-treated and untreated or placebotreated infants.…”
mentioning
confidence: 99%
“…However, we reexamined this question recently and found that CWD does not affect Pes measurements adversely (30,31). Therefore, it can be assumed that the measurements provided here are a reliable reflection of pleural pressure changes.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Despite the well-known methodological problems of esophageal manometry, [24][25][26] measurements of esophageal pressure are a suitable and, for clinical decisions, a reliable method for the assessment of lung mechanics, especially in preterm infants. 27 Combination of esophageal manometry with the FTT improves the usefulness of this technique considerably. An important advantage of the FTT is the possibility to adjust the F I,O 2 and to continuously measure air leaks of the mask.…”
Section: Fig 6 Changes In V T / P Esmax (Absolute Values and Percementioning
confidence: 99%